Intensity modulated radiation therapy (IMRT) for sinonasal tumors: a single center long-term clinical analysis - Askoxylakis, Vasileios; Hegenbarth, Pia; Timke, Carmen; Saleh-Ebrahimi, Ladan; Debus, Jürgen; Röder, Falk; Huber, Peter E. (Radiation oncology, 2016)
Radiotherapy has a central role in the treatment of sinonasal malignancies, either as postoperative or as primary therapy. To study the efficacy and safety of intensity modulated radiotherapy (IMRT) for sinonasal tumors a single center retrospective evaluation focusing on survival and therapy related toxicity was performed.
Gesehen am 19.08.2020